From Standardized Tests to Meaningful Experiences: The Future of Student Assessment - Dhakal , Rebat K. (Education Review Journal, 2025)
This paper critically examines the prevailing dominance of standardized testing in student assessment and explores the global shift toward more meaningful, experience-based evaluation methods. Using a desk-review methodology, the study analyzes assessment practices from a diverse sample of countries including Finland, Estonia, Canada, Australia, New Zealand, Scotland, Sweden, Singapore, India, South Korea, and Japan, that have successfully integrated alternative approaches such as project-based learning, portfolios, and experiential assessments. These methods are shown to enhance student engagement, promote equity, and better prepare learners for real-world challenges by capturing a broader range of skills beyond rote memorization. The paper also discusses the challenges Nepal faces in implementing such alternatives, including resource constraints, teacher capacity, and cultural resistance, while highlighting opportunities presented by ongoing national education reforms. Practical recommendations are offered to support educators and policymakers in redefining educational success through inclusive, formative, and contextually relevant assessment systems. By embracing these innovations, Nepal can foster a more equitable and future-ready education system that values meaningful learning experiences over standardized scores.